Book Review. (1st October 2019) - Alimen, Nazlı
Modern Fashion Traditions: Negotiating Tradition and Modernity through Fashion, M. Angela Jansen and Jennifer Craik (eds) (2016) 1st ed., London and New York: Bloomsbury, 256 pp., 23 b/w illustrations ISBN 978 1 47422 949 4, Hardback, UK £90.00; Paperback, UK £28.99; eBook, UK £31.30